Penerapan Metode Storytelling Berbasis Video dalam Pembelajaran Sejarah Kebudayaan Islam di Sekolah Dasar Negeri 6 Kendari - Muslimat Aulia; Nirwana Natsir; Nurlathifah Thulfitrah B (Jurnal Budi Pekerti Agama Islam, 2026)
This study aims to describe the application of the video-based storytelling method in learning Islamic Cultural History (SKI) in grade V of SDN 6 Kendari, including the stages of planning, implementation, student response, and obstacles faced by teachers. The research uses a qualitative descriptive approach with data collection techniques in the form of participatory observation and semi-structured interviews. The subjects of the study were Islamic Religious Education teachers and grade V students. Data analysis was carried out with the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawn, while the validity of the data was checked through triangulation of sources and techniques. The results of the study showed that the application of video-based storytelling was able to increase student involvement in SKI learning, characterized by enthusiasm, attention, and active participation in discussions. Teachers plan learning by adapting SKI material into the form of stories visualized through video media, then carrying out activities with interactive methods. The obstacles faced include limited technological facilities, variations in students' ability to understand video content, and limited learning time. This study provides a practical overview of the effectiveness and challenges of implementing video-based storytelling as a learning medium for SKI in elementary schools, as well as a consideration for teachers in developing more varied and meaningful learning strategies.